Rapid in situ nondestructive evaluation of lodging risk in dryland agronomic wheat research. (31st August 2022) - Mangin, Amy; Heuschele, Jo; Brûlé‐Babel, Anita; Flaten, Don; Wiersma, Jochum; Lawley, Yvonne
Abstract: The natural occurrence of lodging in wheat ( Triticum aestivum L.) in small‐plot research aiming to record visual ratings is unpredictable highly dependent on environmental conditions, and does not differentiate between root and shoot lodging. Detailed plant characteristics can be used to indicate lodging risk; however, such measurements are destructive and time‐consuming for projects that are not focused solely on evaluating lodging. The Stalker, a push force meter, can be used nondestructively to rapidly indicate stem strength and elasticity, which may be useful for measuring lodging risk in small‐plot research to indicate both root and shoot lodging. The objective of this study was to evaluate the ability of the Stalker to detect agronomic management practices that are known to reduce lodging risk (reduced plant density, split nitrogen applications, and plant growth regulator applications). Stalk strength (resisting force) and elasticity (spike displacement, energy, and power) measurements were taken at anthesis and physiological maturity in a small‐plot agronomic research trial. The Stalker was able to identify practices with high and low lodging risk. Lower plant density led to increased stem strength (measured by resisting force) and stem flexibility (measured by spike displacement) compared with high plant densities, indicating a decreased risk of both stem and root lodging when low plant densities were used. Overall, the Stalker is a new tool for rapid and nondestructive measurements of lodging risk in small‐plot agronomic research trials and can indicate both stem and root lodging risk by measuring indicators of both stem strength and elasticity. Core Ideas: The Stalker is a nondestructive tool for indicating the lodging risk of wheat in agronomic research trials. Stem strength and elasticity indicators can be paired to understand root and shoot lodging risk. Measurements at anthesis are more suited to indicate lodging risk than those at maturity.